Adverse effects of fentanyl/midazolam among patients of intensive care unit (ICU): a narrative review - Septiyanti, Windy; Puspita Sari, Ika; Murti Andayani, Tri (Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada and Indonesian Pharmacologist Association or Ikatan Farmakologi Indonesia (IKAFARI), 2024)
Patients of intensive care unit (ICU) have a complicated condition due to disease, comorbid, and other risk factors. Some ICU patients need to get an invasive process to reduce pain, anxiety, and support their condition. During an invasive process, including mechanical ventilation which causes pain or anxiety, the patient is givensedative and analgesic agents to support the procedure and reduce the patient’s pain and anxiety. However, the use of fentanyl/midazolam has the potential to cause adverse effects, for instance, hypotension, hypoxia, and delirium in several ICU patients. Several risk factors that can lead to adverse effects are aging, obesity, underlying cardiac disease, and the amount of dosage. Therefore, it is essential to recognize the risk factors and monitor the use of fentanyl/midazolam to prevent the worsening condition of patients.